Structural study of joints in Banyas region (Latakia University Journal -Basic Sciences Series, 2019)
Study of joints in Banyas region showed the dominant of tow principal direction NE-SW directions and NW-SE direction, and tow minors directions E-W and N-S. NE-SW and E-W joints is from Pliocene in age and NW-SE joints from Upper Cretaceous in age. The origin of  NE-SW oriented joints is tensional strain accorded with basaltic dykes of the same orientation as that of joints in basalt. The divergence between joints decrease in carbonatic rocks and increase in Pliocene basalt, the aperture of joints decrease in cretaceous carbonatic rocks and increase also in Pliocene basalt.